THE PARTIAL QUANTITATIVE CHANGES OF HANDBALL SPECIFIC MOTOR ABILITIES PRODUCED BY 12-WEEK FITNESS PROGRAM - Melika Muratović,; Haris Pojskić, (Sport Scientific And Practical Aspects, 2025)
The aim of the study was to find out partial quantitative changes of students’ specific handball motor abilities, produced by applied 12-week combined fitness program. All participants were health sport faculty male students with ages 19 ± 1. The experimental program included a three times work out per week, two times resistance, weight training and once a week plyometric training. In order to detect potential changes we conducted paired sample t-test. The obtained results showed that the program has made statistically significant changes on 8 of 9 tests. The highest level of transformation has made on variables for ball handling estimation (28, 20 and 10, 66 %), while the smallest changes are produced on variables for evaluation of movement speed with the ball (2, 87 and 10, 66 %). We think, that fine adjusted training load to all participants, respectively, an individualised approach, contributed to the obtained results. Our opinion is that this kind of fitness program should be a part of regular faculty program during all educational period, in order to enhance students’ basic and specific motor capacities and make their way to improve tehnical elements of different sports, easier.